The Tulude Traditional Ceremony In Christian Perspective - Mychael Dimes Antameng (Psalmoz: A Journal of Creative and Study of Church Music, 2020)
Culture, customs and traditions in people's lives, are no longer seen as taboo or should not be tampered with, because of culture, customs and traditions become a bridge in preaching the gospel. Even the Christian community or church is growing in the midst of customs, culture and traditions. Thus there is a role or fair share of culture in the growth of the gospel message. The gospel penetrates all lines of human life including culture, customs and traditions, because "Jesus Christ comes first in all things". Jesus Christ is superior to all cultures, traditions and customs in the community. God bestows culture, customs and traditions in human life to be able to introduce Himself to people who are very limited in understanding God, so that the gospel can be preached by means of culture, customs and traditions.